PEMBELAJARAN IBADAH SHALAT BAGI ANAK BERKEBUTUHAN KHUSUS (ABK) TUNA GRAHITA DI SLB E NEGERI PEMBINA MEDAN SUMATERA UTARA - Lubis, Khairunnisa; Purba, Hadis; Syukri, Makmur (Universitas Islam Negeri Sumatera Utara Medan, 2024)
are categorized as children with special needs, the author here examines how learning to pray for children with special needs at Pembina Medan Special Special School in North Sumatra by Islamic Religious Education teachers . In this study the authors used descriptive qualitative research with data collection techniques using observation, interviews and documentation. The researcher uses data analysis techniques using Miles and Huberman's theory, which is a theory that proposes an activity in analyzing qualitative data that is carried out interactively and continues continuously until complete. There are 4 kinds of components according to the theory of Miles and Huberman as follows: Data Collection, Data Reduction, Data Presentation, Withdrawal/Verification . The results of this study indicate that the learning that is carried out at the E Negeri Pembina Medan Extraordinary School is prayer. By exemplary and habituation by using demonstration and imitation methods so that children will imitate what a teacher does with a note that they must be guided because they are children who have their own limitations. If children are used to them they will routinely do this without having to receive orders first, so that students will get used to doing these activities.